The application of the Baker-Venkataraman rearrangement to the synthesis of benz[b]indeno[2,1-e]pyran-10,11-dione - Nopporn Thasana (2018)
A tetracyclic benzocyclopentabenzopyran-4-one was synthesized via a domino reaction involving an initial aroyl transfer as in the Baker-Venkataraman rearrangement. The derived 1,3 diketone underwent the intramolecular acylation followed by cyclization to give the product. © 2002 Elsevier Science Ltd. All rights reserved.